LEGAL CERTAINTY IN INDONESIA REGARDING THE MIGRATION OF LAND CERTIFICATES FROM ANALOG TO ELECTRONIC SYSTEMS - Roestamy, Martin; Sitohang, Sudiman; Tama Rahayu, Ray (Al-Mubin, 2025)
The digital transformation of land administration in Indonesia through the migration from analog certificates to electronic certificates represents an effort to modernize public services. This study analyzes the legal implications of this migration, particularly regarding Ownership Rights, in the context of legal certainty and protection for right holders. Using a descriptive normative legal research method, this paper examines relevant regulations, including the Basic Agrarian Law, Government Regulations on land registration, the Electronic Information and Transactions Law, and the Regulation of the Minister of Agrarian Affairs/National Land Agency No. 3 of 2023. The analysis is based on the theory of the rule of law grand theory, legal certainty middle theory, and legal protection applied theory. The findings show that e-Certificates have the potential to improve legal certainty through efficiency, protection against physical risks, and enhanced transparency. However, challenges remain, including the validity of legacy data, cybersecurity risks, the digital divide, and the complexity of implementing a digital system under a negative publication framework. Legal protection is shifting from safeguarding physical documents to securing digital data, privacy, and system accessibility. Strengthening regulations, validating data, enhancing cybersecurity, increasing digital literacy, and developing effective dispute resolution mechanisms are essential to fully realize the benefits of e-Certificates